Perceptions of training on affective commitment and intention to stay - Wong, Mikkay Ei Leen, 1989-, author 631347 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Doktor Falsafah) - Universiti Teknologi Malaysia, 2019